Innovation and Peripherality: A Comparative Study in Six EU Member Countries - Andrew Copus; Dimitris Skuras; Kyriaki Tsegenidi (European Regional Science Association (ERSA), 2006)
The present work compares rates of innovative activity among firms located in peripheral dynamic and central lagging areas of the European Union. Data on 600 businesses located in twelve areas, in six countries of the EU were collected in the framework of an EU- funded research project (Aspatial Peripherality, Innovation and the Rural Economy- AsPIRE- QLK5-2000-00783). Empirical evidence shows that the regional rate of innovative activity is very well predicted by easily observable firm characteristics. Oaxaca-Blinder like decompositions between the difference in rates of innovative activity in peripheral and more central areas are undertaken. Decompositions show that the major part of the observed differential innovative activity rates is unobservable, i.e., it is due to unobserved characteristics and not due to observable firm characteristics. Unobserved characteristics may be either firm specific (human and entrepreneurial capital, etc.) or region specific (institutional environment, social capital, traditional economic factors, etc.) and constitute an unobserved type of innovation specific 'untraded interdependencies'. This conclusion is important for planning policies to support innovation and especially to the regionalization of innovation policies. -
Keywords: 330